The Role of Digital Marketing Strategy in Star Promotion - Taking Taylor as An Example - Zeng, Xinyi (Transactions on Economics, Business and Management Research, 2024)
With the continuous development of network communication technology, information dissemination, and consumption patterns are closely related to smartphones and network marketing, which leads to a shift in celebrity marketing strategies transmitting from traditional media to multi-channel digital marketing. This paper examines Taylor Swift's marketing strategies across different periods through a literature review, comparative analysis, and model evaluation. By comparing Taylor’s marketing strategies over time, the study reveals that digital marketing can enhance fan loyalty and extend a celebrity's peak period of popularity. At the same time, the increasing influence of stars in the industry brought by digital marketing can also help stars enhance their economic value. However, the findings also indicate that excessive use of digital marketing may diminish fan loyalty and reduce fan base. The study showcases the importance of balancing digital marketing efforts to maintain long-term fan engagement and sustain a celebrity's prosperity in the digital market.